Avoidable Hospitalization Trends From Ambulatory Care-Sensitive Conditions in the Public Health System in México - Poblano Verástegui, Ofelia; Torres-Arreola, Laura del Pilar; Flores-Hernández, Sergio; Nevarez Sida, Armando; Saturno Hernández, Pedro J. (Frontiers in Public Health, 2022)
Objectives: To estimate and identify variations in rates of avoidable hospitalizations (AH) by ambulatory care-sensitive conditions (ACSC) in public institutions of the Mexican health system during the period 2010-2017. Methods: Secondary analysis of the base of hospital discharges to the Ministry of Health (MoH) from 2010 to 2017. AH by ACSC was calculated by age and sex per 100,000. Variations between institutions were calculated, Adjusted AH rates were calculated by group of causes . Adjusted AH trend rates were analyzed by Join Point Regression. Results For the period 2010-2017, the AH by ACSC reduced from 676,705 to 612,897, almost 13% to 10.7% of hospital discharges. For SCV, the change remained constant, and in 2015 to 2017, high variation was observed by SCV ≥3. AH from diabetes is the highest and similar to other chronic diseases. Conclusions: Variations are observed by institutions. This variation in CV and SCV among subsystems and states may be due to inequities in the provision of services. The factors that contribute to the load of AH by ACSC in the Mexican Health System requires detailed analysis.